2012
DOI: 10.4161/trns.19998
|View full text |Cite
|
Sign up to set email alerts
|

The endoglycosidase heparanase enters the nucleus of T lymphocytes and modulates H3 methylation at actively transcribed genes via the interplay with key chromatin modifying enzymes

Abstract: (2012) The endoglycosidase heparanase enters the nucleus of T lymphocytes and modulates H3 methylation at actively transcribed genes via the interplay with key chromatin modifying enzymes, Transcription,3:3,[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 79 publications
5
84
0
Order By: Relevance
“…15 In addition to liberating HSPG-bound proteins, heparanase, either by binding to putative cell-surface receptors, or subsequent to its internalization and nuclear entry, has also been suggested to affect gene transcription. 5,[11][12][13][14]33,34 In cancer cells, this property of secreted heparanase can induce cell signalling and gene expression in both parent and adjacent cells, maintaining their survival and delaying demise. 11,16,17,[35][36][37] Our data suggest, for the first time, that HG promotes both the secretion of heparanase from EC as well as its uptake into cardiomyocytes, initiating prosurvival mechanisms to temper the consequences of hyperglycemia in the diabetic heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In addition to liberating HSPG-bound proteins, heparanase, either by binding to putative cell-surface receptors, or subsequent to its internalization and nuclear entry, has also been suggested to affect gene transcription. 5,[11][12][13][14]33,34 In cancer cells, this property of secreted heparanase can induce cell signalling and gene expression in both parent and adjacent cells, maintaining their survival and delaying demise. 11,16,17,[35][36][37] Our data suggest, for the first time, that HG promotes both the secretion of heparanase from EC as well as its uptake into cardiomyocytes, initiating prosurvival mechanisms to temper the consequences of hyperglycemia in the diabetic heart.…”
Section: Discussionmentioning
confidence: 99%
“…5,[7][8][9] Following its nuclear entry, Hep A also influences transcription by cleaving nuclear HSPG, mitigating the suppressive effect of heparan sulphate on histone acetyltransferase. [10][11][12][13][14] More recently, we established a novel role for Hep A in modulating cardiac metabolism during diabetes. 10,15 The above studies in cancer and diabetes fixated on the effects of Hep A , incorrectly assuming that only the HSPG-hydrolyzing ability of heparanase was of importance.…”
Section: In Cancer Biology Hepmentioning
confidence: 99%
“…CXCL10 is therefore a new member in a growing list of genes regulated by heparanase and associated with tumorigenesis (i.e., VEGF, VEGF-C, TF, RANKL, HGF, MMP9). A novel set of genes under heparanase regulation has recently been characterized in T cells 41 . In this context, nuclear heparanase was shown to regulate the transcription of a cohort of inducible immune response genes by controlling histone H3 methylation 41 , further expanding the transcriptional potential of heparanase.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pro-heparanase can induce cell signaling via PI3-kinase-mediated phosphorylation of AKT (38,39) and even act as a transcription factor regulating genes involved in cell differentiation, inflammation, and glucose metabolism (40)(41)(42). Other studies reported that heparanase enzymatic activity upregulates proinflammatory cytokines from human peripheral blood leukocytes (IL-1β, IL-6, IL-8, IL-10, and TNF), as well as mouse splenocytes (IL-6, MCP-1, and TNF) (43).…”
Section: Discussionmentioning
confidence: 99%